A new test method and system for the circumferential deformation of cylindrical standard specimens in geotechnical mechanics and its application. (January 2020) - Liu, Zhongzhong; Wang, Hanpeng; Yuan, Liang; Zhang, Bing; Wang, Wei; Ma, Zhengwei; Xue, Yang; Li, Yong
Graphical abstract: Highlights: A new system was proposed for circumferential deformation of cylindrical standard specimens. This system has clear testing principle, exquisite structure, low cost and high accuracy. Its high reliability and repeatability were verified by comparing with MTS chain extensometer and close-range photogrammetry. It is applied to the coal adsorption degradation test under different adsorption pressures in this paper. This system is important to improve the rock mechanics test method and to upgrade the old testing machine. Abstract: A new test method and system was proposed for circumferential deformation of cylindrical standard specimens. It has clear testing principle, exquisite structure, low cost and high accuracy. Its high reliability and repeatability were verified by comparing with MTS chain extensometer and close-range photogrammetry, and the error between it and MTS method is less than 0.22% in the Poisson's ratio test. This system can be used in gas-solid coupling, triaxial loading and other loading environments and it is applied to the coal adsorption degradation test under different adsorption pressures in this paper. The deformation pattern and the instability failure of coal during loading were obtained, and the influence of the adsorption pressure on volume expansion, coal strength and fracture development was analysed. This system is important to improve the rock mechanics test method and to upgrade the old testing machine.